Cosmeceutical awareness among community pharmacists in Jeddah, Saudi Arabia: The case of sunscreens and moisturizers. (23rd June 2020) - Kurban, Nouf A.; Altwaim, Shada A.; Altayeb, Ghazal A.; Somali, Njood A.; Almehmady, Alshaimaa M.; Alharbi, Waleed S.
Abstract: Background: Although cosmetic products such as sunscreens and moisturizers are generally considered safe, they can be less effective or harmful if used improperly. Thus, pharmacist's awareness about cosmeceuticals is pivotal in counseling about the ingredients and the proper use of such products. Objective: To evaluate the awareness level of community pharmacists regarding cosmetic products particularly sunscreens and moisturizers in Jeddah, Saudi Arabia. Methods: This is a cross‐sectional study conducted on 310 community pharmacists in Jeddah, Saudi Arabia, in the duration (June‐November 2019). Results: With respect to the level of awareness toward sunscreen products, 74% of the participants demonstrated a clear understanding of Sun Protection Factor (SPF). In terms of sunscreen counseling and the impact of these products on drug‐induced photosensitivity, the average awareness of participants was 62% and 55%, respectively. However, only 16% of participants were aware of the expiry date. The average pharmacist's knowledge of the expiration date of the moisturizers and the proper use/ingredients was 86% and 58%, respectively, while only 42% of participants responded correctly to the instructions for application of moisturizers. Cross‐tabulation between the level of education and the need to acquire knowledge about cosmetics has shown that the majority of pharmacists has indicated that they need more knowledge about cosmetics. Conclusion: Around 53% of community pharmacists are aware about the sunscreen part, while 62% have the knowledge about moisturizers. Hence, more cosmetic courses and workshops are recommended to raise level of awareness.